(3eMGVQGJ aj Yde GdEbJUGO (B/s - (3HhMaU, MGcejs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2020)
(3jhLg gPG GdcJGH dWdHI GdSfI GdChdi Ydhe GbJUGOjI fXGe (B((3d(B.(3e(B.(3O(B) (3hjXe hMOGJ ebjGS eONd Gdi Yde GdGbJUGO h GdCacGQ GdJj SHbJ JCSjS Yde GdGbJUGO, HGdGVGaI Gdi GdeOQSI GdcdGSjcjI hJCSjS Yde GdGbJUGO, hGdEbJUGO heQMdI GdKhQI GdcjfjRjI, GdcjGfGJ GdcHQj hGdXhGgQ GdGbJUGOjI GdeYGUQI(B. s
(3GdeQGLY U(B.169 (3feGPL ef GdCSFdI deQGLYI hGdJOQjH Ydi GdELGHI GdfehPLjI U(B.161s
Keywords: (3Yde GdGbJUGOs